Fiscal significance of taxes and fees levied on export-import transactions (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The reforms being implemented today are primarily based on human interests, which can be seen in the effective tax policy being implemented in the development of foreign economic activity, as well as in other sectors. The reforms being implemented in accordance with the principle of "the state is the main reformer" have led to fundamental changes in the sector based on the logic of "not for the sake of reform, but for the sake of the person."